2017
DOI: 10.1248/cpb.c17-00487
|View full text |Cite
|
Sign up to set email alerts
|

Ethereal C–O Bond Cleavage Mediated by Ni(0)-Ate Complex: A DFT Study

Abstract: Density functional theory calculations were performed to explore the mechanism of Ni-catalyzed crosscoupling reactions involving organo-lithium and -zinc reagents through ethereal C-O bond cleavage. Based on this work, together with our previous mechanistic study on etheric Kumada-Tamao reaction, we identify and characterize a novel catalytic cycle for cross-coupling mediated by Ni(0)-ate complex.Key words cross-coupling; ether; nickel catalyst; organolithium; organozinc; density functional theory (DFT) calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 82 publications
2
48
0
Order By: Relevance
“…[7] In addition, nickel catalysts can activate strong s-bonds outside the scope of Pd catalysis,t hus allowing unconventional, but readily available electrophiles,s uch as phenol derivatives,t o be functionalised. [8][9][10] In 1979, Wenkert et al [11] reported that aryl ethers could serve as electrophiles in Kumada-Corriu type cross-coupling reactions with Grignard reagents under Ni catalysis.U nlike aryl esters and other activated phenol-derived electrophiles [8,10] in which the C(sp 2 )ÀOb ond can be cleaved by Ni 0 species,t he direct oxidative addition of aryl ethers is thermodynamically and kinetically unfavourable, [12][13][14][15][16] which suggests that non-conventional mechanisms are in operation, particularly for transformations occurring under mild conditions.W ang, Uchiyama, and co-workers have provided theoretical support for an alternative anionic pathway (Scheme 1) through DFT calculations,w hich identified that anionic Ni 0 -ate complexes are key intermediates that enable C À Ob ond cleavage. [14,16] Nickelate intermediates have been proposed in several Ni-promoted functionalisation reactions, [17][18][19][20] but catalytically relevant examples have rarely been isolated [21] and direct experimental evidence for their role in the anionic pathway has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In addition, nickel catalysts can activate strong s-bonds outside the scope of Pd catalysis,t hus allowing unconventional, but readily available electrophiles,s uch as phenol derivatives,t o be functionalised. [8][9][10] In 1979, Wenkert et al [11] reported that aryl ethers could serve as electrophiles in Kumada-Corriu type cross-coupling reactions with Grignard reagents under Ni catalysis.U nlike aryl esters and other activated phenol-derived electrophiles [8,10] in which the C(sp 2 )ÀOb ond can be cleaved by Ni 0 species,t he direct oxidative addition of aryl ethers is thermodynamically and kinetically unfavourable, [12][13][14][15][16] which suggests that non-conventional mechanisms are in operation, particularly for transformations occurring under mild conditions.W ang, Uchiyama, and co-workers have provided theoretical support for an alternative anionic pathway (Scheme 1) through DFT calculations,w hich identified that anionic Ni 0 -ate complexes are key intermediates that enable C À Ob ond cleavage. [14,16] Nickelate intermediates have been proposed in several Ni-promoted functionalisation reactions, [17][18][19][20] but catalytically relevant examples have rarely been isolated [21] and direct experimental evidence for their role in the anionic pathway has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations of the reaction scope (e.g., organoboron, organozinc, and/or other C–O/C–N electrophiles) and synthetic applications of the present method to photoelectrical materials, are in progress. It should be noted that previous mechanistic studies on transition metal-catalyzed C–O/C–N bond cleavage reactions from our group 27 , 35 , 69 and others 35 , 43 , 46 , 47 , 49 have found that the oxidative addition of ethereal C–O bond to Ni generally suffers from high activation barriers. However, it can be greatly facilitated either by formation of the Ni(0)-ate complex with Grignard reagent or by NHC ligand.…”
Section: Discussionmentioning
confidence: 78%
“…We next turned our attention to other organometallic species. Recently, Rueping, 40 Feringa, 41 and our group 42 43 have reported protocols for ethereal Murahashi-type coupling using organolithiums, which provide high efficiency under mild conditions. When di-lithium reagent 4a prepared by the bromine-lithium exchange reaction of 0a was employed, the polycondensation with 2a took place smoothly at room temperature with Ni(cod)2 catalyst (cod: 1,5-cyclooctadiene) and SIMes ligand (SIMes: 1,3-bis(2,4,6-trimethylphenyl) imidazolidin-2-ylidene), affording 3aa in 80% yield with high molecular weight ( M n = 15.3 kDa, PDI = 1.92) (Table 1 , Entry 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting feature of the CCR of alkenyl sulfoximines is the general necessity of ap romotion by MgBr 2 ,w hich is effective in diethylether but not in THF.T he promotion could be due to ar ate enhancement of the oxidative addition [51] through coordination to the nucleofugal sulfonimidoyl group under formation of complex I-MgBr 2 .R ate acceleration of the Ni 0 -catalyzed CCR by Lewis acids has been previously observed and generally ascribed to an acceleration of the oxidative addition through nucleofugal complexation. [13] We had previously observed a complex formation between allylic (N-methyl)sulfoximines and BF 3 .…”
Section: Salt Promotionmentioning
confidence: 99%